A clinical review and introduction of the diagnostic algorithm for thalidomide embryopathy (DATE). (January 2019) - Mansour, Sahar; Baple, Emma; Hall, Christine M
Thalidomide embryopathy results from the ingestion of thalidomide in the first trimester during pregnancy, causing multiple forms of congenital abnormalities of variable severity that involve all systems. The skeletal findings most frequently affect the limbs, particularly the upper limbs and hands. Increasingly, several genetic disorders with similar birth defects have been identified. New cases of malformations owing to possible exposure to thalidomide continue to present through both historical and current usage. However, inadequate proof of ingestion, marked phenotypic variation and the possibility of an alternative genetic condition, hinder the diagnosis of thalidomide embryopathy. We introduce a 'diagnostic algorithm for thalidomide embryopathy' (DATE) diagnostic software that can potentially provide a numerical score for the likelihood of birth defects in an individual as being caused by exposure to thalidomide and to provide a differential diagnosis based on the pattern of malformation.